Advocacy training tool for pediatric residents to strengthen firearm safety laws - Risney, Scott; Hollon, Hannah; Dodington, James (Frontiers in Pediatrics, 2023)
Firearm injury is the leading cause of death in children and adolescents in the US, surpassing motor vehicle crashes. There is a need for greater legislative advocacy around firearm injury prevention, specifically around safer storage of firearms. A national medical trainee-based program convened in 2021 with the goal of increasing advocacy efforts around common causes of pediatric injury. A focus was to create a set of advocacy training tools that could be utilized by a wide variety of stakeholders. A subgroup sought to design policy-based training tools; one focused on general firearm injury prevention principles and another specifically focused on Child Access Prevention (CAP) laws. We explicate the utility of these documents and the need for greater advocacy around pediatric firearm injuries